264 NEPHROGENIC FIBROSING DERMOPATHY IN THE DIFFERENTIAL OF FIBROSING SKIN DISORDERS. (1st January 2005) - Kim, R. H.; Ahmed, M. M.; Ma, L.; Hayat, S.
Abstract : Background: Nephrogenic fibrosing dermopathy (NFD) is a newly recognized, idiopathic fibrosing skin disorder that occurs in patients with acute or chronic renal failure of no specific etiology. NFD has been reported in patients with and without prior dialysis exposure. It is manifested by progressive cutaneous fibrosis involving the extremities and the trunk with typical sparing of the face and internal organs. We report 2 new cases of NFD in patients with end-stage renal disease (ESRD) on hemodialysis (HD). Purpose: The purpose of this report is to describe 2 additional cases of NFD, to familiarize clinicians with this recently recognized fibrosing skin disorder, and to review its distinguishing clinical and histopathological features from other disorders of cutaneous fibrosis. Case Report 1: A 64 year old black male with diabetes mellitus (DM), hypertension (HTN), coronary artery disease (CAD), peripheral vascular disease (PVD), history of cerebrovascular accident, chronic hepatitis B, chronic pancreatitis, history of alcoholism, and ESRD developed a bullous eruption on his hands approximately 48 hours after initiation of HD. The involved skin became scaly and thickened with progressive proximal extension along the upper extremities, the chest and abdomen, and later the lower extremities. Antinuclear antibodies were negative and evaluation for autoimmune disease was unremarkable. Skin biopsy revealed NFD. Case Report 2: A 44 year old black male with DM, HTN, peptic ulcer disease, PVD, left axillary vein thrombosis (LAVT), history of alcoholism, ESRD, and HD dependence for 3 years presented with recurrent left upper extremity edema 2 years after diagnosis of LAVT. Repeat venous duplex studies at this time were negative. Physical examination revealed thickened, scaly skin involving the hands, forearms, arms, and upper back with flexion contractures of the interphalangeal joints of the hands, wrists, and elbows bilaterally. Histopathology from skin biopsy revealed NFD. Discussion: NFD is a newly recognized fibrosing skin disorder occurring in patients with renal failure. Progressive induration and tightening of the skin appears to be preceded by edema and leads to joint contractures and painful disability. The etiology is unknown and there are no proven effective treatments. There are some reports of NFD improvement with reversal of renal failure or renal transplantation, but not in all cases. Some patients have developed NFD post renal transplantation and development is not exclusive to dialysis exposure. NFD must be distinguished from other clinically similar disorders such as scleroderma, scleromyxedema, and eosinophilic fasciitis, among a myriad of others.